2005
DOI: 10.1103/physrevlett.95.186101
|View full text |Cite
|
Sign up to set email alerts
|

Attracted by Long-Range Electron Correlation: Adenine on Graphite

Abstract: The adsorption of adenine on graphite is analyzed from first-principles calculations as a model case for the interaction between organic molecules and chemically inert surfaces. Within density-functional theory we find no chemical bonding due to ionic or covalent interactions, only a very weak attraction at distances beyond the equilibrium position due to the lowering of the kinetic energy of the valence electrons. Electron exchange and correlation effects are much more important for the stabilization of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
238
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(273 citation statements)
references
References 27 publications
28
238
3
Order By: Relevance
“…We also tried f 42 ͑r͒ and f 81 ͑r͒ in place of f 32 ͑r͒, with f 81 ͑r͒ being the damping function used by Ortmann et al, 37,38 and found that the results for U͑d͒ are almost indistinguishable from those obtained by using f 32 ͑r͒. The vdW interactions vdW ͑r͒ corresponding to f 42 ͑r͒ and f 81 ͑r͒ vanish at r = 0 and are different from that for f 32 ͑r͒ in the short range, but this difference is minimal in the physically relevant range, r Ͼ r CC = 1.42 Å, where r CC is the C-C bond length in the layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also tried f 42 ͑r͒ and f 81 ͑r͒ in place of f 32 ͑r͒, with f 81 ͑r͒ being the damping function used by Ortmann et al, 37,38 and found that the results for U͑d͒ are almost indistinguishable from those obtained by using f 32 ͑r͒. The vdW interactions vdW ͑r͒ corresponding to f 42 ͑r͒ and f 81 ͑r͒ vanish at r = 0 and are different from that for f 32 ͑r͒ in the short range, but this difference is minimal in the physically relevant range, r Ͼ r CC = 1.42 Å, where r CC is the C-C bond length in the layer.…”
Section: Resultsmentioning
confidence: 99%
“…This interpolation scheme was similar to that used by Pacheco and Ramalho 59 and Hasegawa et al 60 in their calculations of the intermolecular potential in C 60 solids. We have no such difficulty in using the GGA calculations, and this is probably the reason why Ortmann et al 37,38 did not use the LDA result in their semiempirical approach but concentrated only on the GGAbased method ͑i.e., GGA+ vdW͒. The modification of f damp ͑r͒ in Eq.…”
Section: Semiempirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…44. Dispersion corrected DFT [45][46][47][48][49] (DFT-D) was among the most popular schemes to incorporate the van der Waals interaction into density functional theory before the emergence of the parameter-free van der Waals density functional 50-52 (vdW-DF) method, which accounts for van der Waals interactions using a correlation term that is a non-local functional of electron density. The vdW-DF method was used to calculate adsorption of Alq 3 molecules on non-magnetic metal surfaces such as Al (Ref.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…The details of the interaction of DNA with CNTs have not yet been fully understood, though it is generally assumed to be mediated by the π-electron networks of the base parts of DNA and the graphene-like surface of CNTs [2,9,10]. It is therefore desirable to obtain a better understanding of the binding mechanism, and the relative strength of base-CNT binding as it is indicated experimentally from sequence-dependent interactions of DNA with CNTs [3,4].…”
Section: Introductionmentioning
confidence: 99%